Prosecutors and politics: a comparative perspective - Tonry, Michael H. (Crime and justice, 2012)
Prosecutors and politics in comparative perspective / Michael Tonry -- Japan's prosecution system / David T. Johnson -- Prosecution and prosecutors in Poland : in quest of independence / Krzysztof Krajewski -- The Dutch prosecution service / Henk van de Bunt and Jean-Louis van Gelder -- The prosecutor in Swedish law / Petter Asp -- Prosecution in Washington State / David Boerner -- Persistent localism in the prosecutor services of North Carolina / Ronald F. Wright -- Prosecution in Arizona : practical problems, prosecutorial accountability, and local solutions / Marc L. Miller and Samantha Caplinger